Effect of Rectal Hygiene on Sexually Transmitted Infections Among HIV-Negative Men Who Have Sex with Men (MSM). (4th October 2017) - Hassan, Adiba; Blumenthal, Jill; Dube, Michael; Ellorin, Eric; Corado, Katya; Moore, David; Morris, Sheldon; ,
Abstract: Background: Rectal gonorrhea (NG) and chlamydia (Connecticut) infections are common among men who have sex with men (MSM). Rectal douching/enema (RDE) is a common practice among MSM that can affect the rectal microbiome. It is unclear if this practice is associated with acquiring rectal infections (RI) with either NG or CT. Methods: From 2013–2015, 398 adult HIV-negative MSM and transwomen were enrolled in a randomized controlled study on text messaging for adherence to pre-exposure prophylaxis (PrEP). Participants were surveyed on sexual behavior, frequency of RDE, drug use, and nutritional habits in conjunction with routine sexually transmitted infection testing. Pearson's χ 2 and two sample t -tests were used to measure significance of RDE and other risk factors with RI. Multivariable logistic regression model was used to control for confounding and assess the association of RDE with RIs. Confounders (i.e., age, number anal receptive sex, number sex partners) were selected a priori for inclusion in the final model based on a causal model and statistical significance. Results: Of 397 participants, 262 (67%) performed RDE and 132 (33%) had at least one NG or CT rectal infection over 48 weeks. Number of condomless anal receptive sex acts (mean = 19, P < 0.001), condom use for anal receptive sex ( P = 0.017), number of male sex partners in past 3 months (mean = 14, P = 0.001), and the use of poppers ( P < 0.001) were associated with RI. There was no significant association between nutritional habits, probiotic foods or supplements and RI, with the exception of energy bars ( P = 0.029). Controlling for confounders, RI was associated with RDE less than weekly with OR = 1.02 (95% CI 0.52–1.99) while RDE weekly or more had OR = 2.08 (95% CI 1.03–4.17). Stratified by number of partners, MSMs with more than the median (>6) number of partners had OR = 4.96 (95% CI 1.29–19.03) if performing RDE less than weekly, and OR = 6.03 (95% CI 1.55–23.49) if weekly or more. Conclusion: Rectal hygiene with douching/enemas is a common practice among MSMs on PrEP, which increases the odds of acquiring rectal NG and/or CT. This finding is suggestive for the use of rectal hygiene products/practices as potential targets for sexually transmitted infection prevention. Disclosures: All authors: No reported disclosures.